Advances on mechanisms of hypothalamic-pituitary-adrenal axis in abnormal glucose metabolism induced by air pollution - Bin PAN; Wenhui YANG; Yanyi XU (环境与职业医学, 2022)
Recently, the adverse health effects of air pollution on human have attracted more and more attentions. Particulate matters (such as PM2.5 and PM10, with aerodynamic diameters ≤2.5 and ≤10 µm, respectively) and ozone are the major ambient pollutants in China. A large number of studies have shown that exposure to particulate matters or ozone induces metabolic abnormalities, such as type 2 diabetes. However, the underlying biological mechanisms are not clear. In this review, we introduced the epidemiological and toxicological research progress of the effects of air pollutants on hypothalamus-pituitary-adrenal (HPA) axis. Considering the critical role of HPA axis in stress response, the molecular mechanisms of HPA axis-mediated glucose metabolism in fat, liver, muscle, and other tissues were also summarized. By integrating relevant literature and references, we proposed that HPA axis may play an important role in the abnormal glucose metabolism caused by air pollution, providing a scientific basis for future studies on the intervention methods of adverse health effects induced by air pollution.